„Obrzezany” Grek i „prawdziwy” Żyd w świetle Rz 1,18-3,20 - Żywica, Zdzisław (Collectanea Theologica, 2017)
The essential Christological and soteriological message of the Letter of St. Paul to the Romans precedes with the reflection on the biblical idea of the retributive justice of God. He does not do it to humiliate Jews and Gentiles because of the sin in which they lapsed, or to make them aware of their equally hopeless situation before God, or even to force them to humiliate themselves in grief and repentance before God the Judge. He wants to explain to the addressees of the letter why God intended to justify them all together in the same way, without taking into account the primacy of the privilege of the Jews, nor the permanent godlessness of the Gentiles. Both were simply sinners, which caused them to find themselves in the same situation with respect to the righteousness of God’s judgment and punishment. Therefore, all without exception, as sinners both Jewish and pagan, will attain justification in the same way, namely by faith in Jesus Christ.